Anatomy of an Experimental Political Stock Market - Forsythe, Robert; Nelson, Forrest D.; Neumann, George R.; Wright, Jack (American Economic Review, 1992)
Results from the Iowa Political Stock Market are analyzed to ascertain how well markets work as aggregators of information. The authors find that the market worked extremely well, dominating opinion polls in forecasting the outcome of the 1988 presidential election, even though traders in the market exhibited substantial amounts of judgment biases. Their explanation is that judgment bias refers to average behavior, while in markets it is marginal traders who influence price. They present evidence that in this market a sufficient number of traders were free of judgment bias so that the market was able to work well. Copyright 1992 by American Economic Association.